ANALISIS PERBANDINGAN ALGORITMA LZW DAN HUFFMAN PADA KOMPRESI FILE GAMBAR BMP DAN PNG - Satyapratama, Andika; Widjianto, Widjianto; Yunus, Mahmud (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
File compression is one of important aspect in the development of information technology. The demands of providing information in a short time with large number and size of files makes compression techniques very important. There are a lot of algorithms that have been developed for the compression of files, including: LZW algorithm and Huffman Algorithm. This study discusses the comparative analysis between the two algorithms are against compressed image file format BMP and PNG. Analysis of this study aims to provide knowledge about what is the best algorithm between both of the algorithm to compress the image file format BMP and PNG. This analysis is comparing the ratio and the estimated time of each algorithm for image file format BMP and PNG. The author uses the Java programming language to implement both LZW and Huffman algorithm, and then analyze the process and results of compression on the file format BMP and PNG. After testing and analysis of experiments the compression process, it is concluded that the compression process BMP and PNG file format, Huffman algorithm can compress files faster than LZW algorithm, but the LZW algorithm can produce better compression ratio than Huffman algorithm.